Analisis Pengaruh Kecepatan, Akurasi, dan Biaya Pengiriman terhadap Kepuasan Pelanggan: Studi Kasus CV Konita Agro Putra - Alam Abdul Salam; Wirawan Widjanarko; Franciscus Dwikotjo Sri Sumantyo (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to research, test and assess the influence of the independent variables Speed, Accuracy and Delivery Costs on the dependent variable customer satisfaction for products from CV Konita Agro Putra. The sample for this research was 110 customers who had used products from CV Konita Agro Putra. This type of research uses a quantitative approach. Data was collected directly from respondents using research instruments in the form of questionnaires via Google Form and purposive sampling techniques. then the data results are processed using the SPSS 24 data processing application. The results of this research prove that there is a significant and positive influence of Delivery Speed on Customer Satisfaction, there is a significant and positive influence of Delivery Accuracy on Customer Satisfaction, there is a significant and positive influence of Delivery Costs on Satisfaction Customers, there is a simultaneous influence between Delivery Speed, Delivery Accuracy and Delivery Costs significantly and positively on Customer Satisfaction.